Interview with Fritjof Capra | Entrevista com Fritjof Capra - Conti, Diego de Melo (Sustentabilidade: Diálogos Interdisciplinares, 2020)
Fritjof Capra, PhD., physicist and systems theorist, is a founding director of the Center for Ecoliteracy in Berkeley, California. He is a Fellow of Schumacher College (UK) and serves on the Council of Earth Charter International. Capra is the author of several international bestsellers, including “The Tao of Physics (1975), “The Web of Life” (1996), and “The Hidden Connections (2002). He is co-author, with Pier Luigi Luisi, of the multidisciplinary textbook, “The Systrems View of Life” (2014). Capra’s online course (www.capracourse.net) is based on his textbook.